Price Transmission Process in Vertical Markets: an Empirical Analysis of Onion Markets in Tamil Nadu State (India) - Rajendran, Srinivasulu (European Journal of Sustainable Development, 2015)
The objective of the paper is to examine price transmission process between wholesale and retail markets by adopting Asymmetric Price Transmission (APT) Model. The paper has taken a case of Onion ((Allium cepa L.) wholesale and retail markets in Tamil Nadu state, India. The paper used wholesale and retail prices data from secondary sources. The results show that high margin at retail and wholesale levels of prices points to possibility of distortion in prices which may lead to an asymmetric process in the vertical market. The speed and magnitude of price changes and also the type of asymmetry in the vertical market system has identified the presence of both positive and negative asymmetry. With respect to speed, where the markets have shown negative asymmetry, there is evidence of retail prices responding much faster to decrease in wholesale prices than to increases in wholesale prices. Where a positive asymmetry holds, the result is the opposite. Keywords: Vegetables, Asymmetry, Efficiency, Market Integration and Symmetry